Emotional States of African Elephants (Loxodonta africana) Kept for Animal–Visitor Interactions, as Perceived by People Differing in Age and Knowledge of the Species - Ilaria Pollastri; Simona Normando; Barbara Contiero; Gregory Vogt; Donatella Gelli; Veronica Sergi; Elena Stagni; Sean Hensman; Elena Mercugliano; Barbara de Mori (Animals, 2021)
This study aimed to investigate how three groups of people of differing ages, and with differing knowledge of the species, perceived the emotional state of African elephants (Loxodonta africana) managed in captive and semi-captive environments. Fifteen video-clips of 18 elephants, observed during three different daily routines (release from and return to the night boma; interactions with visitors), were used for a free choice profiling assessment (FCP) and then analyzed with quantitative methods. A general Procrustes analysis identified two main descriptive dimensions of elephant behavioral expression explaining 27% and 19% of the variability in the children group, 19% and 23.7% in adults, and 21.8% and 17% in the expert group. All the descriptors the observers came up with showed a low level of correlation on the identified dimensions. All three observers’ groups showed a degree of separation between captive and semi-captive management. Spearman analyses showed that stereotypic “trunk swirling” behavior correlated negatively with first dimension (free/friendly versus sad/bored) in the children’s group; second dimension (agitated/confident versus angry/bored) amongst the adults; and first dimension (active/excited versus agitated/bored) amongst the experts. More studies are needed to investigate other potential differences in assessing elephants’ emotional states by visitors of different ages and backgrounds.